Specifics of Using Image Processing Techniques for Blood Smear Analysis - Vyacheslav Lyashenko; Tetiana Sinelnikova; Oleksandr Zeleniy; Asaad Mohammed Ahmed Babker (Newinera Publisher, 2020)
The process of medical diagnosis is an important stage in the study of human health. One of the directions of such diagnostics is the analysis of images of blood smears. In doing so, it is important to use different methods and analysis tools for image processing. It is also important to consider the specificity of blood smear imaging. The paper discusses various methods for analyzing blood smear images. The features of the application of the image processing technique for the analysis of a blood smear are highlighted. The results of processing blood smear images are presented.